Human Security Norms and Reconstruction of Global Governance: Meta-Governance for Human Security - Dr. Yoochul Lee (South Eastern European Journal of Public Health, 2025)
In the past decade, human security has significantly shaped the principles and practices of the United Nations, governments, and NGOs. This paper examines human security as a "compound norm," integrating existing norms like people-centered development and human rights with new standards. This fusion addresses comprehensive issues from non-combatant safety during conflicts to hunger, human rights oppression, environmental degradation, and infectious diseases. The evolving concept highlights tensions between state security and a people-centered approach, and between national sovereignty and humanitarianism. Governance under human security often involves "compound global governance," engaging diverse actors such as governments, international organizations, NGOs, and corporations. Despite varying intensities across areas, these actors form partnerships to align their goals and practices with the aim of ensuring people's safety. This study analyzes the emerging governance characteristics within the human security framework, focusing on the adjustment of regimes and networks across various sectors.